1996
DOI: 10.1034/j.1399-3054.1996.960421.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza formation on Norway spruce (Picea abies) roots affects the pathway of anaplerotic CO2 fixation

Abstract: R. 1996. Myeorrhiza formation on Norway spruce (Picea abies) roots affects the pathway of anaplerotic CO, Activities of carboxylaEion enzymes were analyzed in the mycelium of the mycorrhizal fungus Amanita muscaria (L. ex Fr.) Hooker, in non-myeorrhizal short roots of Norway spruce (Picea abies IL.] Karsl.) and in mycorrhizas of these two partnens. While pyruvate carboxylase (PC, EC 6.4.1.1) and phosphoenolpyruvate carboxykinase activities (PEPCK, EC 4.1.1.49) could be detected in the mycelium of A. muscaria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Hobbie et al . () found that fresh conifer needles were unexpectedly enriched in 14 C, dating to 0–3 years prior to collection, and they discussed the various factors that could account for both this and the similar dating of 14 C in basidiocarps of known mycorrhizal species, including anaplerotic fixation of CO 2 (Wingler et al ., ), internal recycling of C within mycelial systems and uptake of C from soil amino acids by fungi. However, Treseder et al .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Hobbie et al . () found that fresh conifer needles were unexpectedly enriched in 14 C, dating to 0–3 years prior to collection, and they discussed the various factors that could account for both this and the similar dating of 14 C in basidiocarps of known mycorrhizal species, including anaplerotic fixation of CO 2 (Wingler et al ., ), internal recycling of C within mycelial systems and uptake of C from soil amino acids by fungi. However, Treseder et al .…”
Section: Discussionmentioning
confidence: 89%
“…Fungal colonization of senescent or recently dead roots cannot be excluded, since this would also have a recent 14 C signature. Hobbie et al (2002) found that fresh conifer needles were unexpectedly enriched in 14 C, dating to 0-3 years prior to collection, and they discussed the various factors that could account for both this and the similar dating of 14 C in basidiocarps of known mycorrhizal species, including anaplerotic fixation of CO 2 (Wingler et al, 1996), internal recycling of C within mycelial systems and uptake of C from soil amino acids by fungi. However, Treseder et al (2006) found no evidence of transfer of 14 C from labelled litter to ECM fungi.…”
Section: The Biotrophic Status Of Waxcap Fungimentioning
confidence: 99%
“…In plants, phosphoenolpyruvate carboxylase (PEPC) is an important anaplerotic enzyme. Under regular ammonium supply, mycorrhiza formation causes a signi¢cant decrease of both PEPC activity and PEPC protein (Western blot) of roots of spruce seedlings in comparison to the non-mycorrhizal condition [125]. A microhistochemical analysis showed that this e¡ect was most pronounced in the area of most intense interaction of both partners.…”
Section: The E¡ect Of Nitrogen Supply On Plant^fungus Interactionmentioning
confidence: 95%
“…A microhistochemical analysis showed that this e¡ect was most pronounced in the area of most intense interaction of both partners. In parallel, the rates of carboxylation of whole mycorrhizas were signi¢cantly increased, implying that under conditions of symbiosis, ammonium assimilation and thus anaplerotic carboxylation is shifted from the root to the fungus [125]. This is presumably the basis for the transfer of amino acids such as glutamine, glutamate or asparagine from the fungus to the host [17].…”
Section: The E¡ect Of Nitrogen Supply On Plant^fungus Interactionmentioning
confidence: 99%
“…The axenic synthesis of ectomycorrhiza is an important requisite for the investigation of symbiotic interaction on a biochemical or molecular level (Guttenberger and Hampp 1992;Martin and Tagu 1995). From such approaches we now get some idea about plant/fungus metabolic interaction with regard to carbohydrate and nitrogen metabolism (Botton and Chalot 1995;Hampp and Schaeffer 1995;Wingler et al 1996), and molecular regulation (Martin and Tagu 1995).…”
Section: Abstractmamanitamentioning
confidence: 99%